1996
DOI: 10.1007/bf00056558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a model for the effects of substrate interactions on the kinetics of reductive dehalogenation

Abstract: The effects of primary electron-donor and electron-acceptor substrates on the kinetics of TCA biodegradation in sulfate-reducing and methanogenic biofilm reactors are presented. Of the common anaerobic electron-donor substrates that were tested, only formate stimulated the TCA biodegradation rate in both reactors. In the sulfatereducing reactor, glucose also stimulated the reaction rate. The effects of formate and sulfate on TCA biodegradation kinetics were analyzed using a model for primary substrate effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…Dehalobacter strain TCA1 could completely dechlorinate 450 M (60 mg/liter) 1,1,1-TCA to CA in 5 weeks (45); no degradation characteristics have been reported for the mixed culture from which this isolate was obtained. Other studies (8,42,43,54) have reported the degradation of significant amounts of 1,1,1-TCA, but these concentrations were less than those tested in the present study. Therefore, while the current study represents the highest reported 1,1,1-TCA concentration degraded, little data exist for comparison.…”
Section: Discussioncontrasting
confidence: 73%
“…Dehalobacter strain TCA1 could completely dechlorinate 450 M (60 mg/liter) 1,1,1-TCA to CA in 5 weeks (45); no degradation characteristics have been reported for the mixed culture from which this isolate was obtained. Other studies (8,42,43,54) have reported the degradation of significant amounts of 1,1,1-TCA, but these concentrations were less than those tested in the present study. Therefore, while the current study represents the highest reported 1,1,1-TCA concentration degraded, little data exist for comparison.…”
Section: Discussioncontrasting
confidence: 73%
“…This paper describes the complete biological cometabolic transformation of TCA to CA and the conditions necessary for this complete transformation. In general, the rate of cometabolic dechlorination processes increases with an increase in electron donor concentration (Doong and Wu 1996;Wrenn and Rittmann 1996). Here we report that, not only the rate of dechlorination, but also the nature of the products depend on the electron donor concentration.…”
Section: Discussionmentioning
confidence: 55%
“…more TCA was transformed to CA than with methanol as an electron donor. The eect of dierent electron donors on the products of biological dechlorination has never been described, but there are several reports of the eect of dierent electron donors on (the rate of) microbial dechlorination (Bagley and Gossett 1990;Holliger 1992;Lewis and Crawford 1993;Petrovskis et al 1994;Wrenn and Rittmann 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, no inhibition of CH 3 CCl 3 transformation was observed in our packed-bed reactor, since methanogenesis was not suppressed. Wrenn and Rittmann (1996) also reported no e ect of sulfate on CH 3 CCl 3 transformation in a methanogenic bio®lm reactor even at a sulfate/formate ratio of 1. However, in these experiments no time for adaptive changes in the microbial population was allowed.…”
Section: Discussionmentioning
confidence: 96%
“…Only Oldenhuis et al (1989) have reported the partial conversion of CH 3 CCl 3 to trichloroethanol by Methylosinus trichosporium OB3b under aerobic conditions. Transformation of CH 3 CCl 3 in anaerobic continuousow systems has been reported under both sulfatereducing and methanogenic conditions (Bouwer and McCarty 1983;Bouwer and Wright 1988;Cobb and Bouwer 1991;Vogel and McCarty 1987a;Wrenn and Rittmann 1996). Transformation only occurred after a long acclimatization period (10±12 weeks) and was only investigated at CH 3 CCl 3 concentrations below 1 lM.…”
mentioning
confidence: 99%